The Utilization of the Digital RIHANA Application as a Crisis Management Strategy to Build Company Reputation : A Case Study of the Consumer Directorate of Telkom Indonesia - Ginting, Kristha Immanuel Suranta; Syaifuddin, Syaifuddin; Rahman, Abdul (IJOSMAS, 2023)
This research discusses the strategic role of Public Relations in handling trust crises among the public audience within an organization, with a focus on Telkom Indonesia. In crisis management, issue management and internal and external communication are crucial. To handling this, Telkom Indonesia utilizes a digital application called RIHANA as an early warning system to confront communication crises.The aim of this study is to identify crisis management strategies implemented by Public Relations at Telkom Indonesia through the use of RIHANA application and how its utilization can impact the enhancement of the company's reputation. The research methodology employed is qualitative, utilizing the theory of organizational crisis communication as the analytical foundation. The findings reveal that the RIHANA application assists Public Relations at Telkom Indonesia in efficiently and responsively managing customer complaints. The application facilitates the recording and analysis of complaints, enabling the CRM team to take responsive actions based on the nature of each complaint. However, some challenges arise during the implementation of this application, such as incorrect status updates and system errors. Nevertheless, through continuous monitoring and checks, Telkom Indonesia can overcome these challenges and deliver excellent service to enhance customer satisfaction.The RIHANA application serves as an effective tool for Telkom Indonesia to achieve its objectives in crisis communication management and reputation enhancement. Consequently, this research provides insights into the importance of issue management and the utilization of technology in crisis communication handling for companies.